Using Social Media to Engage Communities with Research: Creating a Community Through Best Practices: WC400/AE739, 1/2022 - Williams, Tyus; Stofer, Kathryn A.; Hecht, Kirsten; Lundgren, Lisa (EDIS, 2021)
Creating a community is the way you establish and ultimately present yourself through social media, combining marketing strategy, content production, and community engagement. The objective of this new 5-page publication of the Department of Agricultural Education and Communication is to guide people through the preliminary stages of online community building to engage with a community about science. This document is part of a multipart series on social media titled Using Social Media to Engage Communities with Research. Written by Tyus D. Williams, Kathryn A. Stofer, Lisa Lundgren, and Kirsten Hecht. https://edis.ifas.ufl.edu/wc400